Solar technology for the production of Bi/Pb superconducting ceramics and its properties - Gulamova, D.; Gulamov, Т.; Mamniashvili, G.; Donadze, G.; Peikrishvili, V. (Edelweiss Applied Science and Technology, 2024)
Based on the experience of isostoichiometric and isostructural oxides production using solar energy, the prospects for synthesizing of Bi/Pb superconducting ceramics are shown. The principle of technology in the Large Solar Furnace (Parkent), the influence of gradient conditions on the formation of the oriented structure of crystallites-nuclei, and the connection of the innate properties of precursors with the lamellar morphology and phase composition of massive ceramics are described. The homophase composition of Bi/Pb ceramics was determined. Graphs of resistance and voltage of BSCCO in the temperature range 80-320K are presented. Anomalous of resistance and magnetic susceptibility in bismuth cuprates synthesized by solar energy were observed. Experimental graphs in resistance and magnetic susceptibility changes represent dependencies characteristic of the potential superconducting transitions. The manifestation of the Meissner effect at room temperature and normal atmospheric pressure and daylight, and under the influence of light is shown. The properties of Bi/Pb ceramics are explained by the connection with the innate properties of precursors obtained by concentrated solar energy.